(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى تعرّف واقع استخدام الحاسوب في العملية التعليمية/التعلمية من وجهة نظر عينة من مدرسي وطلبة المرحلة الثانوية في محافظة حماة في الجمهورية العربية السورية, وقد اعتمدت الدراسة المنهج الوصفي التحليلي, واتخذ الباحث من (الاستبانة) أداةً رئيسة لاستقصاء آراء أفراد عيّنة الدراسة المؤلفة من (20) مدرساً ومدرسة و(100) طالباً وطالبة. ـ أشارت النتائج إلى أن للحاسوب أهمية و فائدة كبيرة في زيادة فعالية العملية التعليمية/ التعلمية, مع وجود ضعفٍ في استخدامه من قبل المدرسين. ـ كانت أبرز معوقات استخدام الحاسوب في العملية التعليمية/ التعلمية هي: قلة إقامة دورات تدريبية للمدرسين, وقلة كفاية الوقت المخصص لمادة الحاسوب, وكثرة عدد الطلبة في الصف الواحد. ـ ومن النتائج التي توصل إليها البحث أنه لم تكن هناك فروقٌ ذات دلالة إحصائية عند مستوى دلالة (0.05) في متوسط درجات استجابات المدرسين والطلبة نحو استخدام الحاسوب تبعاً لمتغير الجنس. This study aimed to investigate the reality of using computer in the teaching/learning process from the viewpoint of a sample of teachers and secondary school students in the governorate of Hama in the Syrian Arab Republic. The study had adopted the descriptive analytical approach. The researcher took a main tool of (questionnaire) for investigating the views of study samples consisting of (20) as teachers and (100) students. The results showed that a computer is of great importance and benefit in increasing the effectiveness of the teaching/learning process, with weakness in its use by teachers. The most significant obstacles in the use of computer in the teaching/learning process are: lack of training courses for teachers, lack of sufficient time allotted to computer material, and the large number of students in the class room. There are no statistically significant differences at a significant level of (0.05) in the average scores responses of teachers and students towards using computer according to the gender variable.